The Development of an Application to Design a Solar Updraft Tower Power Plant and to Estimate its Power Generation - Moch. Faqih; Nu Rhahida Arini (VANOS Journal of Mechanical Engineering Education, 2022)
A solar thermal converter is an alternative device to optimize the generation of electricity. One implementation of it is Solar Updraft Tower (SUT) which has some advantages such as easy installation, zero-emission, and long-life investment. This paper aims to describe a method to design the process of a SUT power plant which can be used to predict the expected mechanical power output. The application is built using an open-source computation software, GNU Octave, to produce an interactive user interface. In this paper, data is collected experimentally from SUT prototype in laboratory scale. The operational data is processed using the proposed application to analyze the effect of the variation of inlet diameter on mechanical power output. From the result, the power output increases along with the increasing inlet diameter. The highest power output is produced by a SUT diameter of 0.165 m. This study contributes to increasing the development of renewable energy technology of solar thermal power plants.